Switchpoints : culture change on the fast track for business success - Johnson, Judy, 1971- (Hoboken, NJ : Wiley, 2008)
"SwitchPoints is the story of how Canadian National Railway (CN) advanced from good to great in a few short years, becoming North America's top-performing railroad - a favorite with both corporate customers and investors. Decisions by CN's leaders at critical switchpoints were key, as was the commitment of CN's dynamic CEO in leading the change." "In SwitchPoints, the authors share how company-wide culture change propelled this aging transportation giant to become the profitable powerhouse it is today. Rich with anecdotes, SwitchPoints offers lessons learned and demonstrates the powerful behavioral tools used to change the culture to drive outstanding results in any organization."
"The leadership practices presented here are directly applicable to any business. Even if your enterprise is non-industrial, or your company's culture is very different from CN's, what worked for CN will work for you, too - because behavioral tools apply to all people in any culture, country, language, or industry worldwide. The methods in SwitchPoints apply to any organization and will help enlighten leadership that seeks to improve the bottom line by improving culture."--Jacket
Building one of North America's Top Railroads -- Building one of North America's Top Railroads. The Road to Best-in-Class -- Culture Change on the Fast Track -- Clarifying the Vision -- Clarifying the Vision. CN's Five Guiding Principles -- The Culture of Precision Railroading -- Choosing the Right Switchpoints -- Choosing the Right Switchpoints. How to Change CN's Culture? -- Creating a Culture of Discretionary Performance -- Creating Q4 Leaders to Drive Change -- Selecting the Tools for Change -- Selecting the Tools for Change. The Science of the ABCs -- The Commanding Power of Consequences -- The ABC Toolkit -- Aligning the Switches -- Aligning the Switches. Finding a Champion -- Testing the Business Case -- Gaining Visible Sponsorship: The CEO's Essential Role -- Learning from a Strike -- Planning the Trip -- Making the Case for Change -- Expanding Sponsorship -- Assessing Switchpoints' Impact -- Assessing Switchpoints' Impact. Applying the ABC s: Dressed & Ready -- Early Wins with the ABCs -- Demonstrating Q4 Leadership Through the ABCs -- Life or Death Leadership -- Sawing Our Way to Improvement -- Spiking the Switches -- Spiking the Switches. Leadership Competencies to Support the Change -- Performance Scorecards for Unionized Employees -- Learning through the Railroad MBA -- Hunter Camps Develop Leaders -- The Power of Consistency (17 out of 17) -- Developing Internal Consultants -- Sustaining Culture Change -- Sharing Our Story -- Improving Relations with Our Unions -- Learning from Our Journey -- Learning from Our Journey. Top 10 Tips for Leaders Using the ABC Methodology -- The Culture Change We Achieved -- The Final Word.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Canadian National Railways -- History; Canadian National Railways; Railroads -- Canada -- History; TRANSPORTATION -- Railroads -- Pictorial; Railroads; Canada; History